Financial Performance Analysis of Companies in the Infrastructure Sector Listed on the IDX Before and During the Covid-19 Pandemic - Gulo, Meiman Kristian Putra; Afriliyani, Intan; Lestari, Indah; Azzhari, Suci; Chrisna, Heriyati (Jurnal Riset Ilmu Pendidikan, 2024)
This study aims to analyze the impact of the COVID-19 pandemic on the financial performance of infrastructure sector companies listed on the Indonesia Stock Exchange (IDX). Using a quantitative method with a comparative approach, this study measures financial ratios such as liquidity (Current Ratio, Quick Ratio), solvency (Debt to Equity Ratio, Debt to Asset Ratio), and profitability (Net Profit Margin) in the period before (2019) and during the pandemic (2020). Data were analyzed using the Paired Sample T-Test to identify significant changes. The results showed a significant decrease in average profitability of 30.52 points (p = 0.000), reflecting the major challenges in maintaining net profit during the pandemic. Liquidity increased significantly with an average increase of 158.37 points (p = 0.000), indicating excess current assets due to reduced project activities. However, solvency did not change significantly with a p value of 0.193, indicating stability in the company's funding structure. This study confirms the complex impact of the pandemic on the infrastructure sector, where liquidity increases but profitability decreases, while solvency remains stable. These results provide an empirical basis for formulating policies that support financial management and sustainability of the infrastructure sector.